Lacunary d-statistical convergence and lacunary d-statistical boundedness in metric spaces - Sengul, Hacer; Et, Mikail; Cakalli, Huseyin (Amer Inst Physics, 2019)
In this study, using a lacunary sequence we introduce the concepts of lacunary d-statistically convergent sequences and lacunary d-statistically bounded sequences in general metric spaces.
3rd International Conference of Mathematical Sciences (ICMS) -- SEP 04-08, 2019 -- Maltepe Univ, Istanbul, TURKEY
Keywords: Sequences; series; summability; functional analysis